Migrant youths: Typical aspects of development during the adolescent years, specific challenges of growing up somewhere else, and some things we need to understand better. Issue 176 (9th April 2021) - Noack, Peter
Abstract: The research presented in this Issue impressively documents the great variety of conditions of live that impact child and adolescent migrants' development. The studies conducted in various receiving countries include young refugees as well as the first‐ and second‐generation offspring of migrant families who left their homes in different areas of the globe. Despite this diversity, theories and empirical findings on processes of normative development could be successfully applied, yielding insights into more general aspects of development At the same time, drawing on conceptualizations that were introduced to specifically address experiences and challenges linked to the situation of migrant and minority populations, such as ethnic identity or acculturation, the articles notably contributed to a more comprehensive understanding of migrant adolescents' lives. While the discussion of the studies in this Issue highlights what we have learned, it also points out what we do not know yet, and where future research is needed.